2004
DOI: 10.1088/0029-5515/44/3/008
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-only integral equation approach based on polynomial expansion of plasma current profile to solve the Grad–Shafranov equation

Abstract: A new type of boundary element method has been applied to solve the Grad-Shafranov equation and to give a distribution of magnetic flux function in a Tokamak nuclear fusion device. The quantity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 15 publications
1
21
0
1
Order By: Relevance
“…with ( ) ( ) Itagaki et al [3] showed that the above Grad-Shafranov equation can be transformed into an equivalent boundary-only integral equation in terms of the plasma boundary Γ ,…”
Section: Boundary Integral Equation For the Grad-shafranov Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…with ( ) ( ) Itagaki et al [3] showed that the above Grad-Shafranov equation can be transformed into an equivalent boundary-only integral equation in terms of the plasma boundary Γ ,…”
Section: Boundary Integral Equation For the Grad-shafranov Equationmentioning
confidence: 99%
“…Itagaki et al [3,4] evaluated the total plasma current by directly integrating the polynomial-expanded inhomogeneous term. In the present work the authors propose an alternative technique based on Ampere's circuital law, i.e., a boundary integral of the poloidal field.…”
Section: Introductionmentioning
confidence: 99%
“…Itagaki et al [9] showed that the above Grad-Shafranov equation can be transformed into an equivalent boundary-only integral equation in terms of the plasma boundary Γ ,…”
Section: Boundary-only Integral Equation For the Grad-shafranov Equationmentioning
confidence: 99%
“…This is in general a nonlinear elliptic partial differential equation derived from the ideal MHD equations. There are numerous extensive works in the literature for solving GS equation for the fixed and free boundary problems in the tokamak using the finite element, finite difference, spectral, boundary element and other mesh based methods [2][3][4][5][6][7][8][9]. However the work based on meshless methods applied to the GS equation is very limited.…”
Section: Introductionmentioning
confidence: 99%